A champion of health care for the poor - Hasan, Md. Mahmudul (Media New Age Limited, 2023)
In magnanimity and service to humanity, Dr Zafrullah Chowdhury (1941–2023) dwarfed many people comparable to him in professional background and expertise. His social activism and medical philanthropy for the downtrodden in Bangladesh will remain of enduring value and will continue to play an essential role in society. Early in life he relinquished the glamour of the prospect of a bright medical career in the UK to serve his country and its people. He chose a modest lifestyle that many people of his stature would find freakish, weird and aesthetically unacceptable.